Apelin (APLN) regulates progesterone secretion and oocyte maturation in bovine ovarian cells. Issue 5 (May 2017) - Roche, J; Ramé, C; Reverchon, M; Mellouk, N; Rak, A; Froment, P; Dupont, J
Abstract : APLN and its G-protein coupled receptor APLNR are expressed in the bovine ovary. However their role in granulosa cells and oocytes is unknown. Here, we studied their expression in bovine ovarian cells and investigated their regulation in cultured luteinizing granulosa cells in response to IGF1 and FSH. We determined the effect and the molecular mechanism of APLN (isoforms 17 and 13) on bovine granulosa cell progesterone secretion and on oocyte maturation. By RT-qPCR and immunoblot, we showed that the expression of both APLN and APLNR in granulosa and oocytes significantly increased with ovarian follicles size whereas it was similar in theca interstitial cells. In vitro, in unstimulated luteinizing bovine granulosa cells and in response to IGF1 (10 −8  M) but not to FSH (10 −8  M), we observed that APLN (-17 and -13) (10 −9  M) increased progesterone production; this was abolished in response to the APLNR antagonist ML221. These latter effects were dependent on the MAPK ERK1/2 kinase. Furthermore, we showed that APLN (-17 and -13) (10 −9  M) increased cell proliferation through AKT signaling. Conversely, the addition of APLN-13 and APLN-17 to in vitro maturation medium containing IGF1 (10 −8  M) but not FSH (10 −8  M) arrested most oocytes at the germinal vesicle stage, which was associated with a decrease in progesterone secretion, an inhibition in MAPK ERK1/2 phosphorylation and an increase in PRKA phosphorylation in oocytes. Thus, APLN can increase progesterone secretion and cell proliferation in bovine luteinizing granulosa cells in vitro, while it blocks meiotic progression at the germinal vesicle stage during bovine oocyte in vitro maturation.